HIV adult with fever and shortness of breath: Influenza B misdiagnosed as Pneumocystis (carinii) jiroveci pneumonia (PCP) - Burke A. Cunha; Karishma Chawla; Ismail Jimada (IDCases, 2019)
Clinical correlation is essential in assessing the relevance of the patient’s history and physical findings in making a clinical presumptive diagnosis. False diagnostic associations may result in misdiagnosis.We present a case of an elderly female with HIV on HAART who presented with shortness of breath assumed to have Pneumocystis (carinii) jiroveci pneumonia (PCP) even though she had a clinical diagnosis of influenza B. She was thought to have PCP only because she had HIV. Tests for PCP were negative including BAL staining. Influenza B present in her respiratory secretions by PCR and was also cultured from BAL fluid. Diagnostic associations are helpful in suggesting diagnostic possibilities but must be supported by clinical correlation of characteristic clinical features. Keywords: Ground glass opacities, Viral pneumonia, Elevated LDH, Influenza B pneumonia, HIV and CAP, Eosinophil alveolar exudate, β-1,3 glucan (BG)